2016
DOI: 10.1128/aac.02985-15
|View full text |Cite
|
Sign up to set email alerts
|

Thioridazine as Chemotherapy for Mycobacterium avium Complex Diseases

Abstract: Mycobacterium avium-intracellulare complex (MAC) causes an intractable intracellular infection that presents as chronic pulmonary disease. Currently, therapy consists of ethambutol and macrolides and takes several years to complete. The neuroleptic phenothiazine thioridazine kills mycobacteria by inhibiting the electron transport chain. In several experiments with bacterial populations of up to 1012 CFU/ml, we failed to isolate any bacteria resistant to 3 times the MIC of thioridazine, suggesting the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Thioridazine was also suggested for the treatment of Mycobacterium avium complex (MAC) infections. The number of chronic infections caused by MAC are surpassing tuberculosis in the United States ( Deshpande et al, 2016 ). The proton pump inhibitor omeprazole is effective in several eukaryotic and prokaryotic cells ( da Silva et al, 2011 ) and it also presents antibacterial effects against several bacterial strains including Helicobacter pylori ( Jonkers et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thioridazine was also suggested for the treatment of Mycobacterium avium complex (MAC) infections. The number of chronic infections caused by MAC are surpassing tuberculosis in the United States ( Deshpande et al, 2016 ). The proton pump inhibitor omeprazole is effective in several eukaryotic and prokaryotic cells ( da Silva et al, 2011 ) and it also presents antibacterial effects against several bacterial strains including Helicobacter pylori ( Jonkers et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…A following study on M. avium and M. intracellulare clinical strains from AIDS patients showed that resistance to clarithromycin was significantly reduced in the presence of TZ, CPZ, and VP, and the same EPIs were effective in decreasing the efflux of EtBr from mycobacterial cells; moreover, increased retention of [ 14 C]-erythromycin in the presence of these EPIs further demonstrated that active efflux contributes to MAC resistance to macrolides [42]. A further study evaluated TZ as chemotherapy for MAC diseases by investigating its pharmacokinetics/pharmacodynamics against a reference strain of M. avium [59].…”
Section: Mycobacterium Avium Complex (Mac)mentioning
confidence: 98%
“…Clofazimine dose-response in the HFS-Mkn. The hollow-fiber system model has been used to establish the PK/PD relationships of drugs used to treat M. tuberculosis, MAC, and M. abscessus infections, as well as for M. kansasii (13,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In the HFS-Mkn dose-response studies, the human monocytederived THP-1 monocytes were infected with M. kansasii to get a multiplicity of infection of 10 bacteria per THP-1 cell (10:1).…”
Section: Methodsmentioning
confidence: 99%